Antarctic glacial history and Southern Ocean productivity during the Middle Eocene - Late Oligocene - Villa G.; FIORONI, Chiara; Persico D.; Roberts A. P.; Florindo F. (Rendiconti online della Società Geologica Italiana, 2014)
Paleoclimatology and Paleoceanography of the Southern Ocean